CEO Duality and Financial Performance: Testing the Moderating Role of Firm Age: Evidence from a Developing Economy - Akisimire, Richard; Abaho, Ernest; Tweyongyere, Maureen (Journal of Economics and Behavioral Studies, 2020)
This paper tests the moderating role of firm age on the relationship between Chief Executive Officer (CEO) duality and financial performance among manufacturing firms in Uganda. A cross section survey was adopted using 78 manufacturing firms in Uganda. Data was analyzed using descriptive statistics, correlation and hierarchical regression. Modgraph software was also used to ascertain the validity of the set hypothesis. Results reveal that whether the CEO doubles as chairman of board or not, this does not significantly affect firm Financial Performance. However, as the firms grow older, the role of CEO-Board Chairman duality phenomenon gains significance in determining financial performance. Therefore, as firms grow in age, the CEOs should not be the same as Board chairpersons if firms have to perform well financially. Since only a single research methodological approach was employed in this study, future research can undertake to use a mixed methods approach to provide more detailed insights. Further, a longitudinal approach can also be employed to study financial performance trends among manufacturing firms over years. Entrepreneurs of these firms should put emphasis on proper segregation of the CEO role and those of the board chairman especially as firms grow in age. A moderating role of firm age on the relationship between CEO duality and financial performance was tested among manufacturing firms; previous studies have tended to test the direct or mediating effects.